The social cognition in the neuropsychological assessment of autism. Case study - Escobar Benites, Susan Isabel (2023)
Social cognition is a neurodynamic process that restructures and regulates a person’s social behavior in function of time and space. In recent years, this construct has taken relevance regarding neuropsychological evaluations since it lays the foundations for the approach and forecast of a successful social adaptation in people with autistic condition. This article explores the life of Saya, a three year and ten months old child, whom reflects a slight autist condition. As the main study tool a neuropsychological evaluation was carried out and focused on psychobiology. This evaluation included the social cognition, which analyzes four different systems: social perception, socioaffective, mental attribution and inferential and executive, in order to start her therapeutic process.